Problem „polskości” w londyńskich pismach studenckich („Życie Akademickie” – „Kontynenty”) - Moczkodan, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The first part of the text is an analysis of the category of ‘Polishness’ (its senses, understanding and functioning) with respect to emigrational youth gathered around magazines published in the United Kingdom by Polish students, and then by the literary group The Continents (Kontynenty). We show that among the basic problems connected with The Continents Group one may mention the search for the ways in which national identity could be preserved and then passed on to future generations. The definition of what refugees were supposed to do was different if we compare young emigrants and the older generation (which was shaped and gained maturity before the Second World War). The young generation was open to dialogue, but wanted to redefine the common ideas and search for new paths and means which would be useful in preserving cultural identity. Significantly, both generations were in favour of preserving Polish language and culture. As discussed in the second part of the sketch, this was related to the category of patriotism, as well as back-to-front ‘Polish national vices’. In these areas one may observe disparities between the generations; disparities which come down to the opposition: rational assessment vs. mythologization. The former allows young emigrants, who have no complexes or sense of guilt, to take advantage of the opportunities created by the countries in which they settle, and still not lose their bonds with the nation.
The issue of ‘Polishness’ in the London student magazines (‘Życie Akademickie’ – ‘Kontynenty’)
Keywords: "Kontynenty"; polskość; pokolenie; dialog; The Continents Group; Polishness; generation; dialogue